Layered dissolving microneedles as a need-based delivery system to simultaneously alleviate skin and joint lesions in psoriatic arthritis - Kaiyue Yu; Xiuming Yu; Sisi Cao; Yixuan Wang; Yuanhao Zhai; Fengdie Yang; Xiaoyuan Yang; Yi Lu; Chuanbin Wu; Yuehong Xu (Elsevier, 2021)
Psoriatic arthritis (PsA) is a complicated psoriasis comorbidity with manifestations of psoriatic skin and arthritic joints, and tailoring specific treatment strategies for simultaneously delivering different drugs to different action sites in PsA remains challenging. We developed a need-based layered dissolving microneedle (MN) system loading immunosuppressant tacrolimus (TAC) and anti-inflammatory diclofenac (DIC) in different layers of MNs, i.e., TD-MN, which aims to specifically deliver TAC and DIC to skin and articular cavity, achieving simultaneous alleviation of psoriatic skin and arthritic joint lesions in PsA. In vitro and in vivo skin permeation demonstrated that the inter-layer retained TAC within the skin of ∼100 μm, while the tip-layer delivered DIC up to ∼300 μm into the articular cavity. TD-MN not only efficiently decreased the psoriasis area and severity index scores and recovered the thickened epidermis of imiquimod-induced psoriasis but also alleviated carrageenan/kaolin-induced arthritis even better than DIC injection through reducing joint swelling, muscle atrophy, and cartilage destruction. Importantly, TD-MN significantly inhibited the serum TNF-α and IL-17A in psoriatic and arthritic rats. The results support that this approach represents a promising alternative to multi-administration of different drugs for comorbidity, providing a convenient and effective strategy for meeting the requirements of PsA treatment.